Delivery Costs and Cross-border e-Commerce in the EU Digital Single Market - Néstor Duch-Brown; Mélisande Cardona (European Commission, Joint Research Centre (JRC), 2016)
This paper studies the effects of delivery costs on cross-border e-commerce flows in the EU. For this purpose, we use surveys carried out in 2015 on firms and consumers, to analyse the supply and demand side separately. The paper first offers some descriptive statistics on the issues of delivery and e-commerce. In addition, the paper provides some indirect and descriptive evidence about the effects of delivery costs on cross-border e-commerce. Finally, a more robust econometric analysis is carried out to assess the effects of a hypothetical reduction of concerns about delivery cost on cross-border e-commerce in the EU, from the perspective of both consumers and firms. On the consumers' side, the results indicate that concerns about long delivery times reduce expenditure in other countries more strongly if the consumer has had more experience with shopping in non-neighbouring countries. The results on the supply side indicate that removing delivery cost concerns would increase the overall number of firms selling online across the border by 6.2 percentage points. Similarly, an increase of 5 percentage points would be registered in the volume of online trade. Finally, we compute the implied reduction in cross-border trade costs that would result from a hypothetical policy intervention to eliminate these delivery cost concerns. We plug this trade cost estimate into a macro-sector multi-country CGE model. The macro-economic results indicate that, even though the impact on GDP would be tiny, an important effect would come from reduced overall price levels. Consumer prices would be significantly reduced due to a productivity shock in the retail sector.
Keywords: D12; 330; parcel delivery costs; cross-border e-commerce; digital single market